2018
DOI: 10.1007/s10803-018-3590-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Identity in Autism: Sex Differences in Social Affiliation with Gender Groups

Abstract: High rates of gender variance have been reported in autistic people, with higher variance in autistic females than males. The social component of gender identity may be affected, with autistic females experiencing lower identification with and feeling less positively about their gender groups than controls. We measured gender identification, gender self-esteem, and aspects of gender expression (masculinity and femininity) in autistic natal males and females, and controls (N = 486). We found that autistic peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 57 publications
8
86
1
6
Order By: Relevance
“…In our study a significant part of subjects in Samples 2 and 3 indicated their gender as 'other' or non-binary (total n =36). The non-binary participants scored significantly higher than the males and females; this also corresponds to the prior findings in other national samples [38][39][40] The RAADS-14 Rus and the Big Five personality model…”
Section: Age and Gender Differencessupporting
confidence: 89%
“…In our study a significant part of subjects in Samples 2 and 3 indicated their gender as 'other' or non-binary (total n =36). The non-binary participants scored significantly higher than the males and females; this also corresponds to the prior findings in other national samples [38][39][40] The RAADS-14 Rus and the Big Five personality model…”
Section: Age and Gender Differencessupporting
confidence: 89%
“…Participants recruited from SPARK (n = 881, age = 30.94±7.10 years) were predominantly White (78.7%), female (52.8%), and college-educated (71.6% with at least some college). A sizable portion of this sample (9.2%) also identified as a non-binary gender, reflecting the known increase in gender variance seen in individuals with ASD (Cooper et al, 2018). Eighty-two percent of the SPARK sample reported at least one current professionally diagnosed psychiatric condition other than ASD (i.e., they had experienced symptoms of the condition within the last three months or were receiving ongoing treatment for that condition), with a median of 2 current comorbidities (IQR = [1, 4]).…”
Section: Demographicsmentioning
confidence: 91%
“…Secondly, most research into gender and camouflaging has used a binary approach to gender, comparing the experiences and behaviours of males and females. While this is of relevance to the concept of a female autism phenotype, in contrast to the often male-biased diagnostic criteria and assessment tools, this approach ignores the substantial minority of autistic individuals who report a non-binary or fluid gender identity (Cooper et al 2018;Dewinter et al 2017). It also raises issues regarding the appropriateness of male and female norms for transgender autistic individuals, who may have experiences of living and interacting as different genders in different stages of life (Strang et al 2018).…”
Section: Future Directions For Researchmentioning
confidence: 99%